1998
DOI: 10.1111/j.1472-8206.1998.tb00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial β‐adrenergic reactivity in pressure overload‐induced cardiac hypertrophy in the rat

Abstract: The purpose of this study was to evaluate the changes in myocardial beta-adrenergic reactivity in animals undergoing a 4 week cardiac pressure-overload. Abdominal aortic constriction (AAC) or sham operation (sham) were performed in male Wistar rats, and 4 weeks later, isoprenaline dose-effects (chronotropic, inotropic and lusitropic properties) were studied after pithing. Noradrenaline (NA) and adrenaline (A) concentrations and NA turn-over index (DHPG /NE ratio) were evaluated in heart ventricles, while beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
2
0
3
Order By: Relevance
“…In heart failure resulting from myocardial infarction in rat, the down-regulation is mainly due to a selective ␤ 1 -AR decrease without change in K d (Rutger et al, 2000). In cardiac hypertrophy due to abdominal ascending aortic banding, the ␤ 1 -AR downregulation occurs together with a reduced ␤ 1 /␤ 2 ratio (Communal et al, 1998). In this study, as expected, we observed a significant decrease in ␤ 1 -AR density, which paralleled the rise in plasma BNP and thus the severity of heart failure.…”
Section: Discussionsupporting
confidence: 87%
“…In heart failure resulting from myocardial infarction in rat, the down-regulation is mainly due to a selective ␤ 1 -AR decrease without change in K d (Rutger et al, 2000). In cardiac hypertrophy due to abdominal ascending aortic banding, the ␤ 1 -AR downregulation occurs together with a reduced ␤ 1 /␤ 2 ratio (Communal et al, 1998). In this study, as expected, we observed a significant decrease in ␤ 1 -AR density, which paralleled the rise in plasma BNP and thus the severity of heart failure.…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, reports from others 25,39 suggest an attenuated response of volume overload‐induced failing hearts to β‐adrenoceptor stimulation. Downregulation of β‐adrenoceptor stimulation was also reported in failing hearts induced by pressure overload 44 and myocardial infarction 45 . Downregulation of β‐adrenoceptor stimulation in failing hearts following chronic volume overload was attributed to reduced β 1 ‐adrenoceptor density, diminished adenylyl cyclase activity and decreased expression of G sα ‐proteins 46,47 .…”
Section: Discussionmentioning
confidence: 89%
“…It is known that the total number of myocardial β-ARs is closely related to catecholamine levels but a selective decrease in β 1 -ARs has usually been observed during cardiac hypertrophy. The vast majority of studies focused on this issue were done in the LV (Galinier et al 1992;Communal et al 1998;Sethi et al 2007). For RV hypertrophy, a significant decrease in the total number of β-ARs was also reported but receptor subtypes were not discriminated in these early studies (Ishikawa et al 1991;Yoshie et al 1994;Mardon et al 1998).…”
Section: Discussionmentioning
confidence: 99%